О некоторых особенностях понимания “промысла” и “судьбы” в христианской мысли поздней античности [Grigorij I. Benevich: On Some Aspects of Christian Teaching on Providence and Fate in Late Antiquity] - Беневич, Г.И. (Hyperboreus, 2013)
This paper examines the way Christian thought of Late Antiquity transformed the theory of providence and fate found in pagan philosophy. It shows that the concept of fate was not rejected by Christian thinkers (as it is commonly believed), but that it underwent a long process of transformation. Several important Christian thinkers have been studied in this context, among them Justin Martyr, Clement of Alexandria, Eusebius of Caesarea, Nemesius of Emessa, Evagrius and Maximus the Confessor. Special attention is paid to Nemesius’s constructive criticism of the Middle Platonists’ teaching on fate and necessity. It is shown that Maximus the Confessor’s theory of providence and judgment may be treated as a Christian alternative to theory of providence and fate found in pagan philosophy (especially in the Platonists). Maximus did receive his notions of God’s providence and judgment from Evagrius, but he modiﬁed his concepts, so they were no longer a variation of a common Platonic myth, which was typical of both Evagrius and Origen. From Nemesius, Maximus received his deﬁnition of providence elaborated in a dialogue with Middle Platonists. Unlike many other Christian authors, Maximus understood God’s judgment not only as a moral judgment and punishment or reward, but predominantly as an act of ontological differentiation and maintenance of individuals and species in their unique features and movement towards God. Maximus’s theory of providence and judgment presupposed a dynamic view of a world order, which was a fulﬁllment of God’s plan. Unlike his pagan predecessors, particularly Hierocles (whose views are also discussed in the paper), Maximus did not make God’s judgment and justice some “lower” deity or force in comparison with providence. In Maximus, both God’s providential care for the world and for each human being and God’s judgment (understood in its ontological dimension) were equally and eternally belonging to One God, as were His two main forces directed towards His creation.